Brown Bodies, Brown Worlds: Creating Cadence and Crafting Karma - Menon, Jinny (Journal of the Motherhood Initiative for Research and Community Involvement, 2021)
Seeking to trouble monolithic (and at times pejorative) constructions of South Asian girls and females, as part of my doctoral research I engaged in a long term multiperspectival narrative inquiry (Clandinin) into the storied experiences of two girls, their mothers and teacher over the span of several years. My research puzzles were shaped and contoured by the experiences I embody as a woman of colour, a South Asian daughter born, raised, educated, and living in Canada. In the unfolding of this research, in ethical relationship with co-learners, we narratively inquired into our experiences of identity-making and identity-living as crafting an artistry of our lives by shifting away from more traditional and presupposed understandings of academic research. In doing so, this study illuminated and honoured different artful and feminist ways of knowing, being, and learning (Menon, An Artful Narrative Inquiry) infused within a narrative understanding of social justice (Caine et al.). To invite these multifarious ways of knowing and living, I deliberately invoked artwork spaces to create, think, and muse personally and collectively. I came to call this type of engagement heart-full work (Menon, A Story Cloth). Within this relational space of this piece, selected heart-full musings paired with poetry are brought forward to highlight the nuanced experiences of South Asian girls and women, as daughters and mothers who are empowered (O’Reilly, Outlaw(ing) Motherhood, 20) creative, agentic, and artistic architects of our respective coloured worlds (Menon, An Artful Narrative Inquiry).